2014
DOI: 10.1002/jbmr.2432
|View full text |Cite
|
Sign up to set email alerts
|

PTH Signaling During Exercise Contributes to Bone Adaptation

Abstract: Improving the structural integrity of bone reduces fracture risk and development of osteoporosis later in life. Exercise can increase the mechanical properties of bone, and this increase is often attributed to the dynamic loading created during exercise. However, the increase in systemic PTH levels during exercise gives reason to hypothesize that PTH signaling also regulates bone adaptation in response to exercise. Therefore, the first aim of this study was to establish the impact PTH signaling has on bone ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 54 publications
7
42
0
Order By: Relevance
“…The differences in response to iPTH and exercise in G 11 -Tg mice suggest that factors other than PTH were regulating exercise-induced decreases in osteoclasts, and these were not affected by increased Ga 11 expression in osteoblasts. Alternatively, if PTH mediates Previous reports have demonstrated that both iPTH and mechanical strain increase bone formation, but add bone in different magnitudes [9,19]. Consistent with these previous results, the iPTH treatment in this study resulted in significantly greater bone gain than changes in mechanical loading, whereas exercise only slightly increased cortical bone volume and did not increase peak load in WT mice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The differences in response to iPTH and exercise in G 11 -Tg mice suggest that factors other than PTH were regulating exercise-induced decreases in osteoclasts, and these were not affected by increased Ga 11 expression in osteoblasts. Alternatively, if PTH mediates Previous reports have demonstrated that both iPTH and mechanical strain increase bone formation, but add bone in different magnitudes [9,19]. Consistent with these previous results, the iPTH treatment in this study resulted in significantly greater bone gain than changes in mechanical loading, whereas exercise only slightly increased cortical bone volume and did not increase peak load in WT mice.…”
Section: Discussionsupporting
confidence: 92%
“…It has been previously shown that mice with constitutively active Ga q in osteoblasts lack a skeletal response to iPTH [12]. Additionally, Gardinier et al recently proposed that PTH signaling is important for bone adaptation during exercise [9]. Therefore, we employed our transgenic mice overexpressing normal Ga 11 to evaluate the influence of elevated Ga 11 on responses to these osteoanabolic regimens, presumably through the actions of PTH, and investigated their effects on altering bone structure, strength, and cellularity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to mechanical loading, exercise causes changes in systemic and local hormone concentrations, which might facilitate local skeletal adaptation to increased mechanical loading [14]. For example, PTH released during exercise controls osteocyte gene expression [29], and PTH signaling is associated with increased bone formation and improved structural and material properties [29]. Exercise also increases circulating IGF-I, the source of which is the liver or extrahepatic tissues.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is limited understanding of how exercise influences the mechanical properties of bone, given that increased mineral content or bone quantity does not always translate into improved mechanical function (Hui et al, 1988). To this end, animal studies have identified structural and tissue-level mechanical properties that increase during various forms of exercise, such as swimming, jumping, voluntary running in a cage wheel or running on a treadmill (Gardinier et al, 2015; Hoshi et al, 1998; Huang et al, 2003; Iwamoto et al, 2004; Iwamoto et al, 1999; Kohn et al, 2009). For example, young adult mice running on a treadmill consistently exhibit increased structural and tissue-level properties, such as post-yield properties of the tibia (Gardinier et al, 2015; Hoshi et al, 1998; McNerny et al, 2015; Wallace et al, 2010; Wallace et al, 2009).…”
Section: Introductionmentioning
confidence: 99%